Mary I. Ingraham, Joseph K. So, and Roy Moodley, eds. 2016. Opera in a Multicultural World: Coloniality, Culture, Performance. New York: Routledge - Forner, Jane (Columbia University, 2018)
Opera scholars have had something of a bounty in recent years. Opera in a Multicultural World: Coloniality, Culture, Performance follows in a line of collected volumes that have sought to diversify the field through critical focuses on race, identity, colonialism, and gender, including Opera Indigene: Re/presenting First Nations and Indigenous Cultures (2011, edited by Pamela Karantonis and Dylan Robinson), Blackness in Opera (2012, edited by Naomi André, Karen Bryan, and Eric Saylor), and Masculinity in Opera (2013, edited by Philip Purvis). Such works are foundational to the present volume through their emphatic efforts not only to bring these issues to the forefront and consolidate academic work scattered across (and separated by) disciplinary and historical boundaries, but also for their expansion of operatic methodologies. Chapters written by performers and composers sit alongside traditional analyses, bringing into dialogue a welcome diversity of perspectives and conceptual approaches. Uniting seemingly disparate objects of study around common themes, Opera in a Multicultural World promises much: multiculturalism, coloniality, culture, genre, and performance are all touched upon, though condensed to the space of only a few hundred pages. While, like the aforementioned volumes, the book suffers slightly from this topical magnitude, such collections have brought to attention both the enormous potential scope for further work and the clear benefits of multi-disciplinary approaches. Indeed, given the three editors’ contrasting disciplinary backgrounds—musicology, anthropology, and psychology—it is clear that amalgamating and juxtaposing historical, analytical, and sociological research approaches has been a positive influence in shaping the present volume.